HLA class I associations of ankylosing spondylitis in the white population in the United Kingdom. - Brown, M; Pile, K; Kennedy, L; Calin, A; Darke, C; Bell, J; Wordsworth, B; Cornélis, F (1996)
OBJECTIVE: To investigate the HLA class I associations of ankylosing spondylitis (AS) in the white population, with particular reference to HLA-B27 subtypes. METHODS: HLA-B27 and -B60 typing was performed in 284 white patients with AS. Allele frequencies of HLA-B27 and HLA-B60 from 5926 white bone marrow donors were used for comparison. HLA-B27 subtyping was performed by single strand conformation polymorphism (SSCP) in all HLA-B27 positive AS patients, and 154 HLA-B27 positive ethnically matched blood donors. RESULTS: The strong association of HLA-B27 and AS was confirmed (odds ratio (OR) 171, 95% confidence interval (CI) 135 to 218; p < 10(-99)). The association of HLA-B60 with AS was confirmed in HLA-B27 positive cases (OR 3.6, 95% CI 2.1 to 6.3; p < 5 x 10(-5)), and a similar association was demonstrated in HLA-B27 negative AS (OR 3.5, 95% CI 1.1 to 11.4; p < 0.05). No significant difference was observed in the frequencies of HLA-B27 allelic subtypes in patients and controls (HLA-B*2702, three of 172 patients v five of 154 controls; HLA-B*2705, 169 of 172 patients v 147 of 154 controls; HLA-B*2708, none of 172 patients v two of 154 controls), and no novel HLA-B27 alleles were detected. CONCLUSION: HLA-B27 and -B60 are associated with susceptibility to AS, but differences in HLA-B27 subtype do not affect susceptibility to AS in this white population.